The Utilization of Media in the Learning Process of Environmental Education for Building Awareness of the Elementary Students - Indriyani Rachman; Toru Matsumoto; Yayoi Kodama; Dedi Abdul Hadi (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2016)
Abstract Environment Education (or the Pendidikan Lingkungan Hidup-PLH) is expected to be one of the instruments that can raise the awareness of students in communicating with nature. Therefore, the teaching method is very important in delivering this material, so PLH will be interesting for students and achieving optimum results. This paper will demonstrate the results of Problem Based Learning by using certain media, including Story Telling Method, Role Play Method, Outdoor Learning Method, and Kamishibai Card Method in the learning process of PLH in 4 schools at Balikpapan, Bandung and Medan. The result shows that utilization of media as the methods in PLH will be more easily understood by the students. Abstrak Pendidikan Lingkungan (atau Pendidikan Lingkungan Hidup-PLH) diharapkan bisa menjadi salah satu instrumen yang dapat meningkatkan kesadaran siswa dalam berkomunikasi dengan alam. Oleh karena itu, metode pengajaran sangat penting dalam menyampaikan materi ini, sehingga PLH akan menarik bagi siswa dan mencapai hasil yang optimal. Makalah ini akan menunjukkan hasil Pembelajaran Berbasis Masalah dengan menggunakan media tertentu, termasuk Metode bercerita, Metode Bermain Peran, Metode Pembelajaran Luar Ruangan, dan Metode Kartu Kamishibai dalam proses pembelajaran PLH di 4 sekolah di Balikpapan, Bandung dan Medan. Hasil penelitian menunjukkan bahwa pemanfaatan media sebagai metode PLH akan lebih mudah dipahami oleh siswa. How to Cite : Rachman, I. Matsumoto, T. Kodama, Y. Hadi D., A. (2016). The Utilization of Media in the Learning Process of Environmental Education for Building Awareness of the Elementary Students. TARBIYA: Journal of Education in Muslim Society, 3(2), 158-167. doi:10.15408/tjems.v3i2.5423. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v3i2.5423